Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kota Makassar - Aulia Eka Sukmawati (STIM LASHARAN JAYA MAKASSAR, 2017)
Aulia Eka Sukmawati. Influence of Work Motivation and Work Environment to Performance Employee of Population and Civil Registration Office of Makassar City (guided by Baharuddin S and Aminuddin). The study was conducted with the objectives of: (1) To analyze and explain the effect of Work Motivation on the performance of personnel of the Department of Population and Civil Registration of Makassar City. (2) To analyze and explain the effect of the Work Environment on the performance of personnel of the Department of Population and Civil Registration of Makassar City. The results showed that (1) Work Motivation has a positive and significant effect on the performance of personnel of the Department of Population and Civil Registration of Makassar City with a significance value of 0.005 with a coefficient value of 0.259 or 25.9%. These findings indicate that the higher the work motivation of employees cause the higher performance of employees at the Department of Population and Civil Registration of Makassar City. Then the first hypothesis accepted (2) Working Environment employee posistif influence and significant employee performance with significance value of 0,000 with regression coefficient value of 0.245 or 24.5%. This indicates that the Better Working Environment of Employees will improve the performance of employees of the Office of Population and Civil Registration of Makassar, then it indicates that the second hypothesis in this study is accepted.